Acoustic field alteration in a 100 Hz dual acoustic driver straight tube travelling wave thermoacoustic heat pump for thermoacoustic heat transport control. (April 2020) - Widyaparaga, A.; Hiromatsu, T.; Deendarlianto,; Kohno, M.; Takata, Y.
Highlights: A dual speaker thermoacoustic heat pump was constructed for frequency of 100 Hz. Acoustic field was controlled by varying the magnitude and phase difference between speakers. Thermoacoustic heat transport was improved when the values of impedances and impedance phase between the ends of the regenerator were matched. Variation of phase featured acoustic power flow and thermoacoustic heat transport characteristics markedly different in comparison to higher frequency experiments due to differences in impedance and impedance phase matching between the ends of the regenerator. Abstract: A dual acoustic driver thermoacoustic heat pump was constructed to investigate the effect of acoustic field control on travelling wave thermoacoustic heat transport at a frequency of 100 Hz. The acoustic field was controlled by varying the phase difference and magnitude between the two drivers. Variation of phase difference demonstrated the change of both acoustic power flow direction and standing-travelling wave characteristics. Maximum temperature differences obtained between the ends of the regenerator were 23 °C and 19 °C when the acoustic power was flowing in the negative and positive directions, respectively. It has been shown that matching impedances on the cold and hot side of the regenerator influence the thermoacoustic heat pumping characteristics. Where monodirectional acoustic flow was observed on both sides of the regenerator, the impedance angles also coincided well. Variation of magnitude displayed a trend in which activation of an opposing acoustic driver at weaker power enhanced acoustic power flow and heat transport. A maximum temperature difference between the hot and cold sections of 23 °C is obtained when the input electric power of the opposing acoustic driver was 17% of the power of the initial acoustic driver where the impedances and impedance angles on both ends of the regenerator are matched but the acoustic field travelling wave characteristics are still sufficient for travelling wave device operation.